Oceanographic regime shift during 1997 in Disko Bay, Western Greenland - Marc Overgaard Hansen; Torkel Gissel Nielsen; Colin A. Stedmon; Peter Munk (Limnology and Oceanography, 2012)
Data from a long time series of temperature, salinity, and nutrient measurements in Disko Bay (West Greenland) reveal a marked change in the water characteristics during recent years. Seasonal dynamics in the upper 150 m of the water column were highly affected by the seasonality in meteorological conditions, while the deeper water strata were more stable and were primarily influenced by large‐scale circulation patterns. There was a marked increase in the average water temperatures at 200‐m depth in spring 1997, with the long‐term average increasing from 1.30°C to 2.25°C. Weekly data from 1996 to 1997 show that the sudden change in bottom water occurred in April 1997, due to the inflow of a larger proportion of North Atlantic water, which propagated north along the coast before entering the bay. Further support for this inflow was found when tracing the relative proportion of Atlantic water in the bay, using inorganic nutrients. These changes in the oceanography of the bay will not only lead to further glacial retreat but will also affect the local marine ecosystem by changing the relative dominance of major copepod species that overwinter in bottom waters of the bay.